The late Roman grave from Zidani Gaber above Mihovo - Breščak, Danilo; Lovenjak, Milan; Verbič, Tomaž; Leben-Seljak, Petra (Arheološki vestnik, 2002)
This article discusses the late Roman inhumation grave in a sarcophagus, discovered in 1999 on the slope of Zidani Gaber above Mihovo by local inhabitants while removing logs. At Zidani Gaber, where late Roman graves were discovered as early as the end of the 19th century, an elevated fortification was created in the 5th century that existed up to the 7th century. The newly discovered sarcophagus was buried sometime in this period within the fortress. It contained the bones of a female between 24 and 28 years old. Nothing is known of any possible grave goods or decorative objects. The sarcophagus was composed of two refashioned stone cinerary urns, which came from some earlier Roman period cemetery in the vicinity. An inscription was carved on one, with the names of four male individuals from the mid 2nd century or more likely from the 3rd century. In addition to information about the circumstances of the find, descriptions are presented of the cinerary urns and the lid of the sarcophagus, along with the reconstruction of the funerary inscription, the geological analysis of the stone, and the anthropological analysis of the bone remains.